Princesas e infantas solo canto yo: la princesa as an example of musical intertextuality in 18th century popular theatre Madrid. - Soriano Santacruz, Antonio (Cuadernos de Música Iberoamericana, 2023)
Princesas were choral pieces that were used in numerous comedias. They are, therefore, a type of intertextual music that musicology has overlooked. This article will present an analysis of the musical sources needed for them to be properly defined, as well as details regarding their history and survival. It will also investigate the practice that allowed a princesa to move from one comedia to another, essentially based on the Siglo de Oro tradition of writing choruses in stanzas of four eight-syllable verses. This will shed light on a musical term used in eighteenth-century popular theatre in Madrid that is unknown today.
Keywords: music theatre; comedia Madrid; eighteenth century; princesa; musical intertextuality